Electrocardiogram (ECG) changes and cardiac biomarker abnormalities among two marathon runners - Minns, A. B.; Clark, R. F. (The Journal of Emergency Medicine, 2008)
Background: Marathon running has surged in popularity in the last quarter century. A small percentage of marathon runners develop increases of myocardial-specific markers with exercise, sometimes in the diagnostic range for acute myocardial infarction. A spectrum of abnormal electrocardiogram (ECG) patterns has also been described. Objective: ECG change specifically after marathon running has not been reported and may further the understanding of the interrelation of intense physical exertion and cardiac structure and function. Case Report: Two patients who presented to the Emergency Department on June 3, 2007 after participating in an inner-city full marathon (26.2 miles) with very similar abnormal ECGs that met criteria for acute myocardial infarction were included in this case report. Cardiac biomarker analysis and ECGs were recorded. Both runners were admitted to the hospital and underwent coronary catheterization. One runner (Runner 1) had no coronary artery disease on catheterization and his troponin I peaked at 0.3 ng/mL. The other runner (Runner 2) had 99% occlusion of his left anterior descending artery and his troponin I peaked at 13.4 ng/mL. Conclusion: Previously asymptomatic individuals under extreme physical exertion may be at risk for myocardial stress and myocyte injury. Abnormal ECG patterns in patients under these conditions may not correlate with structural cardiovascular disease.